Specific receptor for hydrazine: mapping the in situ release of hydrazine in live cells and in an in vitro enzymatic assay - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Mogare, Devraj G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2016)
We report a new chemodosimetric reagent capable of detecting hydrazine in the presence of several other competing amine derivatives and ionic analytes of biological relevance. This reagent has been utilized for real time monitoring of in situ N2H4 release during the metabolism of a crucial tuberculosis drug, isoniazid, in live HepG2 cells. The fluorescence response of the reagent based on its specific reaction with N2H4 is used for developing an in vitro assay for aminoacylase-1.